ARADIGMATICS OF SYNTAXEMS REPRESENTED BY MONOVALENT COMPONENTS INSTEAD OF THE PREDICATIVE OF THE CORE 1 (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
This article describes syntaxemes representing monovalent syntactic units, their variants, and the possibilities of combining them with other syntaxemes in English sentences. It was found that the univalent nuclear predicative 1 components express 7 different syntaxemes within the framework of substantiality, 2 different syntaxemes in the processual base, and can combine with 4 different processual, 2 different substantial, and 2 different qualifying syntaxemes. It also provides a brief overview of the development of syntaxeme analysis. The article may be of interest to researchers involved in functional linguistics as well as English language learners.